2020
DOI: 10.4314/jard.v18i1.8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of maize-soybean intercropping systems and fertilizer rates on maize grain yield using competitive indices

Abstract: Field trials were conducted in savanna ecologies of Nigeria during the 2015 and 2016 seasons using maize (PVA8) and soybean (TGX 1448-2E) intercropping systems with different fertilizer rates to evaluate the yield of maize and assess the best intercropping system for resource management. Single plant stands and two plants/stand and 2 arrangements of rows (one row on a ridge and two rows on a ridge) were used to impose maize plant densities evaluated in strip inter-crop with soybean. The trial was factorial, la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Generally, maize had higher relative crowding coefficient (Km) value than haricot bean Kb indicating that maize is more competitive than its associate haricot bean (Banik et al, 2000, Dhima et al, 2007 [3,6] (Table 6). The negative K values for maize during 2020 and 2021 season and that of haricot bean during 2020 season suggest that in this mixture there was no yield advantage or disadvantage (Takim, 2012) [27] . With delayed time of haricot bean intercropping, the Km value are above one during both 2020 and 2021 seasons, indicating yield advantages of maize over haricot bean in this intercropping system.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, maize had higher relative crowding coefficient (Km) value than haricot bean Kb indicating that maize is more competitive than its associate haricot bean (Banik et al, 2000, Dhima et al, 2007 [3,6] (Table 6). The negative K values for maize during 2020 and 2021 season and that of haricot bean during 2020 season suggest that in this mixture there was no yield advantage or disadvantage (Takim, 2012) [27] . With delayed time of haricot bean intercropping, the Km value are above one during both 2020 and 2021 seasons, indicating yield advantages of maize over haricot bean in this intercropping system.…”
Section: Discussionmentioning
confidence: 99%
“…According to a report by Dhonde et al [26], green and dry fodder maize and the cropping systems for solitary maize and maize + cowpea at a ratio of 2:2 were uniformly superior to the other systems. Similarly, Takim et al [27] reported that 1228 (2023) 012027 IOP Publishing doi:10.1088/1755-1315/1228/1/012027 4 intercropping sweetcorn and vegetable soybean plant hill -1 and two-row soybean yielded good yields, specifically 4.04 tons ha-1 of corn and 1.34 tons ha-1 of soybeans. This is further confirmed by Li et al [28] .…”
Section: Interaction Between Density Plant and Npk Fertilizer On Fres...mentioning
confidence: 96%
“…These claims were evident above 100 kg N/ha level of application for NPK fertilizer and OF applications. Studies have indicated that applications of organic combined with chemical fertilizers optimized soil quality, stabilized crop yield, and enhanced crop adaptation to climate change(Menšík et al, 2019).The lower yield observed for maize and soybean in the intercrop compared to the sole crop was in consonance withTakim et al (2019). Applying fertilizer containing Ca at the early flowering stage of soybean helps to enhance days to 50% flowering and sustain pod formation in soybean for better performance.Original scientific paper DOI: /10.5513/JCEA01/24.3.3753 Adeola et al: Performances of maize and soybean as influenced by intercropping and fertilizer...…”
mentioning
confidence: 97%